THE EFFECT OF PRODUCT, PROMOTION, LOCATION, AND PRICE OF HALAL CERTIFICATION IN PIE SUSU DEWATA BALI: PENGARUH PRODUK, PROMOSI, LOKASI, DAN HARGA DENGAN SERTIFIKASI HALAL DI PIE SUSU DEWATA BALI - ABU SIRI (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2023)
Labeling halal certificate on Pie Susu is a typical food from Bali which is famous and is a souvenir like Pie Susu Dewata very important For done , so bring enhancement production sales . Study This use approach participatory direct researcher with approach quantitative with results research showing that this product has experienced rapid development after having a halal label on its product packaging. Turnover goes up, products are better known, promotions are more, and sales are up. This is the advantage of a halal certificate that makes consumers trust.